2021
DOI: 10.1155/2021/6186011
|View full text |Cite|
|
Sign up to set email alerts
|

Neural Function Recovery and Safety of Mild Hypothermia Therapy Combined with Monosialotetrahexosylganglioside on Neonatal Asphyxia Complicated by Hypoxic Ischemic Encephalopathy

Abstract: Objective. To explore the effect and safety of mild hypothermia therapy combined with monosialotetrahexosylganglioside (GM1) on neural function recovery of neonatal asphyxia complicated by hypoxic ischemic encephalopathy (HIE). Methods. The clinical data of 90 neonates with HIE were retrospectively analyzed. According to the treatment methods, the neonates were divided into a routine group, a mild hypothermia group, and a combination group, with 30 cases in each group. The differences in neural function recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Mild hypothermia treatment, for example, may successfully enhance neurological function and decrease the inflammatory response in children with HIE. Furthermore, regular hypothermia treatment for HIE children carries the risk of respiratory failure, which is linked to oxygen deficiency caused by ischemic hypoxia episodes (26). So that the results show that treating newborn HIE with a combination of mild hypothermia and EPO seems to be successful.…”
Section: T-testmentioning
confidence: 94%
“…Mild hypothermia treatment, for example, may successfully enhance neurological function and decrease the inflammatory response in children with HIE. Furthermore, regular hypothermia treatment for HIE children carries the risk of respiratory failure, which is linked to oxygen deficiency caused by ischemic hypoxia episodes (26). So that the results show that treating newborn HIE with a combination of mild hypothermia and EPO seems to be successful.…”
Section: T-testmentioning
confidence: 94%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%